Bilateral striopallidodentate calcinosis presenting with psychiatric symptoms and speech disorders - GÜNAL, DİLEK; ULUÇ, KAYIHAN (WILEY-BLACKWELL, 2012)
Ozdilek B, Uluc K, Gunal DI. Bilateral striopallidodentate calcinosis presenting with psychiatric symptoms and speech disorders. Background: Bilateral striopallidodentate calcinosis (BSPDC), also known as Fahr's disease, is a rare neurodegenerative disorder characterised by the deposition of calcium and other minerals in the basal ganglia, centrum semiovale and cerebellum. It is usually idiopathic. Its clinical manifestations vary from asymptomatic individuals to neuropsychiatric abnormalities, movement disorders, cerebellar symptoms and cognitive impairments. Methods: Five cases of BSPDC all of which include psychiatric symptoms and speech problems from two families are documented in this article. Conclusion: The most important diagnostic marker is the demonstration of symmetrical intracranial calcifications. Computerised tomography of the brain is the most frequently used radiologic method to diagnose BSPDC.
Keywords: bilateral striopallidodentate calcinosis; cranial computed tomography; psychiatric symptoms; speech disorders; BASAL GANGLIA CALCIFICATION; FAHRS-SYNDROME; COMPUTED-TOMOGRAPHY; DISEASE; DEMENTIA